Effects of exercise timing on metabolic health - Martínez-Montoro, José Ignacio; Benítez-Porres, Javier; Tinahones-Madueño, Francisco José; Ortega-Gómez, Almudena; Murri, Mora (Wiley, 2023)
The increasing prevalence of metabolic syndrome is associated with major health and socioeconomic consequences. Currently, physical exercise, together with dietary interventions, is the mainstay of the treatment of obesity and related metabolic complications. Although exercise training includes different modalities, with variable intensity, duration, volume, or frequency, which may have a distinct impact on several characteristics related to metabolic syndrome, the potential effects of exercise timing on metabolic health are yet to be fully elucidated. Remarkably, promising results with regard to this topic have been reported in the last few years. Similar to other time-based interventions, including nutritional therapy or drug administration, time-of-day-based exercise may become a useful approach for the management of metabolic disorders. In this article, we review the role of exercise timing in metabolic health and discuss the potential mechanisms that could drive the metabolic-related benefits of physical exercise performed in a time-dependent manner.
Keywords: Ejercicio físico - Aspectos fisiológicos; Metabolismo - Alteraciones; Chronobiology; Exercise timing; Metabolic syndrome; Physical exercise